À la recherche des prémices d’une culture de l’intime - Françoise Simonet-Tenant (Itinéraires, 2009)
In our contemporary era, which turned all that is intimate into its maxim to the point of becoming meaningless, it is difficult to picture the time when the culture of intimacy came into being. Here, we will seek understanding of the notion through its historical authenticity. The culture of intimacy developed during the eighteenth century : it emerged, among others, through the secularisation of a dialogue of confession as in the style of the closing, visible within the confines of private life. Aspiring to intimacy specifically characterised certain writing practices. To believe that the letter and the journal have always conveyed the intimacy of their writers is a largely fictitious view. We will analyse how the path of historical changes in letters met that of personal journals, which then became (first the letter, then the journal) essential tools for the small-scale manufacture of intimacy.